First Evidence of Fungal Strains Isolated and Identified from Naphtha Storage Tanks and Transporting Pipelines in Venezuelan Oil Facilities - Naranjo Briceño, Leopoldo (2015)
Biocorrosion, as well as the biodeterioration of crude oil and its derivatives, is one of the major environmental, operational and economic problems in the Venezuelan oil industry. Fungal contaminants are able to produce large quantities of biomass and synthesize peroxides and organic acids, causing severe damage on metal surfaces and promoting the contamination and biodeterioration of fuels. No evidences regarding fungal strains have been reported to be associated to petroleum naphtha, widely used as a diluent of extra heavy crude oil (EHCO) in the exploitation pro- cesses of the Orinoco Oil Belt, the biggest proven reserve of EHCO worldwide. The aims of this paper were to isolate and identify fungal strains from the naphtha storage tank and the naphtha distribution network from an oil field operator in Venezuela. The results showed the isolation of four different fungal strains. The molecular identification by 28S rRNA sequencing and phylogenetic tree analysis allowed us to identify the presence of: 1) a new uncultured Ascomycota fungus species BM-103, with high identity to novel hyphomycetes Noosia banksiae and Sporidesmium tengii, in the naphtha storage tank; 2) two yeasts, Rhodotorula mucilaginosa BM-104 (Phylum Basidiomycota) and Wickerhamia sp. BM-105 (Phylum Ascomycota), in a highly damaged naphtha pipeline branch and; 3) Cladosporium cladosporioides BM-102 (Phylum Ascomycota) in a cluster oil well. DNA fingerprinting analysis using ERIC-PCR primers pairs also allowed us to detect the presence of R. mucilaginosa BM-104 right in the access of the studied naphtha system. Interestingly, R. mucilaginosa and C. cladosporioides were previously reported as predominant fungal contaminants of diesel and jet fuel and of kerosene and fuel storage systems, respectively. This paper represents the first evidence of fungal strains isolated and identified from the naphtha systems in the Venezuelan oil industry. The results obtained are discussed.